1999
DOI: 10.1122/1.551065
|View full text |Cite
|
Sign up to set email alerts
|

Steady-shear viscosity of stirred yogurts with varying ropiness

Abstract: Stirred yogurt was viewed as a concentrated dispersion of aggregates consisting of protein particles. The steady-shear behavior of three types of stirred yogurt with varying ropiness was investigated experimentally. To describe the shear-dependent viscosity, a microrheological model was used which was developed for weakly aggregating dispersions. This model was capable of successfully describing the steady-state viscosity as a function of shear rate of the stirred yogurts, the protein concentration of which ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 23 publications
4
41
1
Order By: Relevance
“…Under N 2 -H 2 condition, the gel was as weak as under oxidizing conditions despite there being a greater production of EPS. The contribution of EPS produced by LAB to the rheological properties of yoghurt is a common assumption (Hess, Roberts, & Ziegler, 1997;Rawson & Marshall, 1997; van Marle, van den Ende, de Kruif, & Mellema, 1999) but, as reported by Hassan et al (1995) and van Marle (1998), and in the present case, no correlation between the viscosity of fermented milk and EPS concentration was found.…”
Section: Apparent Viscositycontrasting
confidence: 43%
“…Under N 2 -H 2 condition, the gel was as weak as under oxidizing conditions despite there being a greater production of EPS. The contribution of EPS produced by LAB to the rheological properties of yoghurt is a common assumption (Hess, Roberts, & Ziegler, 1997;Rawson & Marshall, 1997; van Marle, van den Ende, de Kruif, & Mellema, 1999) but, as reported by Hassan et al (1995) and van Marle (1998), and in the present case, no correlation between the viscosity of fermented milk and EPS concentration was found.…”
Section: Apparent Viscositycontrasting
confidence: 43%
“…Indeed, the gel of yoghurts produced under N2 -H2 conditions is weaker despite greater EPS production [23]. It is a common assumption that EPS produced by bacteria contribute to the rheological properties of yoghurt [31][32][33] but, as reported by Hassan et al [34], van Marle [35] and Martin et al [23], no correlation between the viscosity of yoghurt and EPS concentrations was found.…”
Section: Effect Of Eh On a Non-fat Yoghurtmentioning
confidence: 38%
“…It exhibits irreversible timedependent shear behaviour, and shear rate thinning (van Marle et al 1999 andRascon-Diaz et al 2012). Rascon-Diaz et al (2012) suggested that, visual inspection of the viscosity curves of fresh yoghurt and reconstituted natural yoghurt (without added hydrocolloids) subjected to spray drying, indicates a decrease in viscosity in both yoghurt samples.…”
Section: Resultsmentioning
confidence: 99%